The Relationship Between Social Support and Stress in Adolescents (16-18 Years) Victims of Bullying at Pondok Modern - Palupi, Dyah Ayu Retno (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Bullying is a negative action that is often aggressive and manipulative, carried one person even more for others during the period in which the physical and non-physical. This study aims to determine the relatioship of social support with stress levels of victims of bullying. This research is a quantitative-research using cross-sectional descriptive design that held on March 18, 2018 at Pondok Modern Al-rifa'ie1 Ketawang Gondanglegi. Samples taken by random sampling consisted of 63 adolescents who fulfilled inclusion and exclusion criteria. Data was collected using social support questionnaires and stress questionnaires. The result of statistical test using Spearman test got p-value 0,002 <? (0,05), hence there is correlation between social support with stress level in adolescent (16-18 year) victim bullying. The results found that 21% of the sample had good category social support, 30% experienced sufficient social support, 49% experienced less social support, and the results found that 33% stress levels were in the mild category, 41% stress level was in moderate category, stress 26% in weight category. Victim of bullying should get social support form giving input, giving motivation, giving attention from friends to reduce stress level on teenager bullying victims like anxiety in him.